2014
DOI: 10.1016/j.csite.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wavy-wall phase shift on thermal-hydraulic performance of Al2O3–water nanofluid flow in sinusoidal-wavy channel

Abstract: a b s t r a c tIn this paper, laminar forced convection flow of Al 2 O 3 -water nanofluid in sinusoidal-wavy channel is numerically studied. The two-dimensional governing equations of continuity, momentum and energy equations in body-fitted coordinates are solved using finite volume method. The sinusoidal-wavy channel with four different phase shifts of 01, 451, 901 and 1801 are considered in this study. The results of numerical solution are obtained for Reynolds number and nanoparticle volume fractions ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Results show that using the nanoparticles under pulsating flow promotes the thermal performance. The effect of the Al 2 O 3 -water nanofluid flow on performance of the sinusoidal-wavy channel with different wall phase shifts was investigated by Ahmed et al [10]. Results indicate that the optimal performance is achieved by 0°phase shift channel over the ranges of Reynolds number and nanoparticle volume fraction.…”
Section: Introductionmentioning
confidence: 97%
“…Results show that using the nanoparticles under pulsating flow promotes the thermal performance. The effect of the Al 2 O 3 -water nanofluid flow on performance of the sinusoidal-wavy channel with different wall phase shifts was investigated by Ahmed et al [10]. Results indicate that the optimal performance is achieved by 0°phase shift channel over the ranges of Reynolds number and nanoparticle volume fraction.…”
Section: Introductionmentioning
confidence: 97%
“…The heat transfer behavior of nanofluids is analyzed in this study by evaluating several fundamental parameters, such as local Nusselt number, mean Nusselt number, non-dimensional pressure drop and thermal enhancement factor. Specifically, we define the local Nusselt number at each solid wall of the channel as referred to the thermal conductivity of the base fluid [45,63]. Therefore:…”
Section: Resultsmentioning
confidence: 99%
“…For example, the PEC values enhance by about 61%, 71%, and 72% by increasing the nanoparticle concentration in the range of 0 to 0.04 for the straight, triangular, and sinusoidal ducts, respectively. Ahmed et al [42,43] showed that the PEC for wavy channels increases with an increase in the nanoparticle volume fraction for the laminar regime. As shown in Fig.15, the wavy ducts have higher values of PEC in comparison with the straight one for the cases in which nanofluid has been used.…”
Section: First and Second Laws Design Considerationsmentioning
confidence: 99%